2022
DOI: 10.1002/ehf2.13993
|View full text |Cite
|
Sign up to set email alerts
|

Role of depressive symptoms in the prognosis of heart failure and its potential clinical predictors

Abstract: AimsThis study aims to analyse the factors associated with prognosis in hospitalized patients with heart failure, particularly the role of depressive symptoms, and to develop a prediction model for depressive symptoms based on clinical characteristics in hospitalized patients with heart failure. Methods and results Baseline information was collected at admission, and patients were followed up after discharge. The endpoint events were being hospitalized for heart failure or all-cause death. Depressive symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…Our outcome was in line with Yang (et al’s, 2021) results that low BMI ( β = −0.116, p = 0.049) was a risk factor for depressive symptoms in patients with CHF, and consistent with a recent study (Duan et al, 2022) that obesity (OR = 0.27, CI = 0.09–0.77, p = 0.015) was independently related to depressive symptoms in hospitalized patients with HF. The possible reasons why low BMI may lead to depressive symptoms in patients with CHF are as follows: previous studies (Qing et al, 2021) showed that patients with CHF accompanied by loss of appetite had a higher risk of depression.…”
Section: Discussionsupporting
confidence: 93%
“…Our outcome was in line with Yang (et al’s, 2021) results that low BMI ( β = −0.116, p = 0.049) was a risk factor for depressive symptoms in patients with CHF, and consistent with a recent study (Duan et al, 2022) that obesity (OR = 0.27, CI = 0.09–0.77, p = 0.015) was independently related to depressive symptoms in hospitalized patients with HF. The possible reasons why low BMI may lead to depressive symptoms in patients with CHF are as follows: previous studies (Qing et al, 2021) showed that patients with CHF accompanied by loss of appetite had a higher risk of depression.…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, screening for depression in HF with traditional questionnaires is complex and challenging due to the overlap of HF symptoms and risk factors for depression, so the objective indicators for assessing depressive symptoms in hospitalized patients with HF are necessary. A study showed that the risk of depression in hospitalized HF patients can be identified by a predictive model consisting of six predictor variables, including history of CVD hospitalization, obesity, renal insufficiency, NT-proBNP (lnNT-proBNP), N (%), and RDW [ 37 ]. Thirdly, the current treatment of depression in HF patients is not fully effective.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have already demonstrated a poor medical prognosis for patients suffering from both conditions [45,46]. A kind of dose-response relationship has been proposed between the severity of depression and cardiac prognosis in depressed patients [47,48], and conversely, an increase in depressive symptoms has been observed in patients with CVD [46,49]. Investigating the biological mechanisms underlining this bidirectional relationship, some animal and human studies have hypothesised that BDNF might play a mediating role in the onset of one of these two diseases because lower serum BDNF levels were observed in patients of both CVD and depression [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%